1991
DOI: 10.1103/physrevlett.66.1422
|View full text |Cite
|
Sign up to set email alerts
|

Kaleidoscopic spatial instability: Bifurcations of optical transverse solitary waves

Abstract: The cell-exit transverse profile for one-way propagation through sodium vapor forms a pattern of spots with complexity and beauty rivaling that of a kaleidoscope. These patterns are stationary in time, reproduce completely when the power or frequency is scanned, and agree well with one-way computations that show that the patterns change very little after one-fifth of the propagation distance, i.e., they exhibit the properties of bifurcations of transverse solitary waves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 17 publications
1
11
1
Order By: Relevance
“…We observed ring structures, splitting of the beam into two partial beams, as well as more complicated structures. These instabilities resemble closely the kaleidoscopic spatial instabilities which Grantham et al observed by introducing aberrations into the beam [33]. They indicate that the stabilization of the self-trapped beam by the saturation process and t.he nonlinear response of the medium is effective only in a limited parameter range.…”
Section: ~ Dieter Suter and Tilo Blasbergsupporting
confidence: 63%
“…We observed ring structures, splitting of the beam into two partial beams, as well as more complicated structures. These instabilities resemble closely the kaleidoscopic spatial instabilities which Grantham et al observed by introducing aberrations into the beam [33]. They indicate that the stabilization of the self-trapped beam by the saturation process and t.he nonlinear response of the medium is effective only in a limited parameter range.…”
Section: ~ Dieter Suter and Tilo Blasbergsupporting
confidence: 63%
“…This regime valid for larger optical thickness will be considered in this letter. Note that in contrast to past observation of pattern formation in hot atomic vapors [19,20] the instabilities based on the coupling to the atomic motion do not require non linear optical response of the atoms.…”
mentioning
confidence: 81%
“…This may be done via an 552 H.-G. Purwins et al 5a. R 2 Alkali vapours in an extended cells Figure 47(a) [283][284][285][286][287][288][289] Stat. pattern in the laboratory system Self-focussing One or more entering beams with vanishing and nonvanishing vorticity Along optical axis: rotation, clusters, fusion, breakup into many spots, interaction of LSs D % 50 mm additional dye cell at position 3 that in turn is pumped by an external laser 4 [260].…”
Section: Saturable Absorbersmentioning
confidence: 99%